2017
DOI: 10.1038/s41598-017-01999-4
|View full text |Cite
|
Sign up to set email alerts
|

A-Kinase Anchoring Protein 79/150 Scaffolds Transient Receptor Potential A 1 Phosphorylation and Sensitization by Metabotropic Glutamate Receptor Activation

Abstract: Mechanical pain serves as a base clinical symptom for many of the world’s most debilitating syndromes. Ion channels expressed by peripheral sensory neurons largely contribute to mechanical hypersensitivity. Transient Receptor Potential A 1 (TRPA1) is a ligand-gated ion channel that contributes to inflammatory mechanical hypersensitivity, yet little is known as to the post-translational mechanism behind its somatosensitization. Here, we utilize biochemical, electrophysiological, and behavioral measures to demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 81 publications
2
46
0
1
Order By: Relevance
“…1,27 Since these kinases are known to be involved in sensitization of TRP channels, 28,29 we investigated the role of PKA and PKC in | 291 1,27 Since these kinases are known to be involved in sensitization of TRP channels, 28,29 we investigated the role of PKA and PKC in | 291…”
Section: Sensory Neuron Type-dependent Sensitization Of Trpa1 Respomentioning
confidence: 99%
See 2 more Smart Citations
“…1,27 Since these kinases are known to be involved in sensitization of TRP channels, 28,29 we investigated the role of PKA and PKC in | 291 1,27 Since these kinases are known to be involved in sensitization of TRP channels, 28,29 we investigated the role of PKA and PKC in | 291…”
Section: Sensory Neuron Type-dependent Sensitization Of Trpa1 Respomentioning
confidence: 99%
“…Then, the plasmids containing mutated TRPV1 (WT TRPV1 size is 90kDa 18,35,36 ) were co-expressed with WT TRPA1 (WT TRPA1 size is 120 kDa 18,28,35,36 ) in CHO cells. Then, the plasmids containing mutated TRPV1 (WT TRPV1 size is 90kDa 18,35,36 ) were co-expressed with WT TRPA1 (WT TRPA1 size is 120 kDa 18,28,35,36 ) in CHO cells.…”
Section: Identification Of Interaction Domains For the Trpa1-trpv1 mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that a carboplatin-induced increase in sensitivity to TRPA1 was significantly decreased by not only a PKA inhibitor but also an AKAP inhibitor ( Figures 5 and 6). AKAP, a scaffolding protein, is required for PKA activation, and it enhances the sensitization of several receptors and ion channels via PKA [38][39][40][41]. Brackley et al [41] have reported that AKAP facilitates phosphorylation of TRPA1, and increases the sensitivity of DRG neurons to TRPA1.…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 is demonstrated to be cold sensitive [61] and plays roles in both cold transduction and mechanotransduction in cutaneous sensory neurons. AKAP 79/150 facilitates phosphorylation and sensitization of TRPA1 in peripheral sensory neurons, resulting in persistent mechanical hypersensitivity [62]. Another study also indicated that TRPA1 activation could co-sensitize TRPV1 channels [60].…”
Section: Other Trp Receptorsmentioning
confidence: 98%